Integrating Acehnese Local Wisdom into Interactive Arabic E-Module: A Design-Based Study Using Digital Flipbook Platform - Aina Salsabila; J. Nurhawani; Nabila Handayani; Anisaturrahmi Anisaturrahmi (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2026)
Although local wisdom has been widely integrated into flipbook e-modules across various disciplines, similar efforts remain scarce in Arabic language education particularly for the Acehnese context. This design-based study developed such a module and evaluated its feasibility, practicality, and effectiveness. Using the ADDIE model with 30 PGMI students (purposive sampling), data were analyzed using descriptive statistics, N-Gain, paired-sample t-test, and Cohen's d. The results were: material expert validation 4.65 (very feasible), media expert 4.75, student response 4.78 (very good). N-Gain was 0.72 (high), with a significant t-test (t(29)=8.94; p<0.001) and a large effect size (Cohen's d=1.63). Due to the absence of a control group, these findings indicate a strong positive trend rather than absolute causal evidence. Theoretically, this study extends the Cognitive Theory of Multimedia Learning through the cultural bridge hypothesis: culturally familiar content activates pre-existing knowledge schemata, reduces cognitive load, and strengthens dual-channel processing (verbal and visual). Globally, this module offers a replicable model for integrating indigenous knowledge into foreign language instruction, addressing cultural disconnects in non-Arab Muslim-majority countries. This research confirms that combining interactive flipbook technology with local wisdom is an effective strategy for creating relevant, engaging, and impactful language learning for the digital generation.